Does the Board of Commissioners’ Characteristics Relevant to the Sustainable Finance Disclosure in Indonesian Banks? - Rahayu Rahayu; Djuminah Djuminah (Journal of Accounting and Investment, 2022)
Research aims: This study aims to investigate empirical evidence of the board of commissioners’ characteristics (independent commissioners, educational level of the president commissioner, and board of commissioner meetings) on sustainable finance disclosure.Design/Methodology/Approach: This study used panel data regression with 205 observations distributed in balanced panel data. The main data analysis was 164 data in 2015-2018, as the voluntary disclosure period. In addition, additional analysis was carried out for 41 data in 2019 as a mandatory disclosure period to achieve robust results.Research findings: The regression results revealed that the independent commissioners and board of commissioner meetings had a significant positive effect on sustainable finance disclosure. Meanwhile, the educational level of the president commissioner did not show a significant effect on sustainable finance disclosure. In additional tests, the educational level of the president commissioner and board of commissioner meetings did not affect the sustainable finance disclosure after being mandatory. Theoretical contribution/Originality: The results of this study can be used as additional support for agency theory and stakeholder theory. Moreover, to the best of the authors' knowledge, this research is the first to use The Financial Services Authority (OJK) regulation 51/POJK.03/2017 as a guideline to measure sustainable finance disclosure. Practitioner/Policy implication: The research result can be used by OJK to evaluate regarding banking commitments in disclosing sustainable finance in Indonesia. Research limitation/Implication: The weakness in this study is the measurement of sustainable finance disclosure using content analysis techniques so that there is an element of author subjectivity in it. For further research, it is hoped that several readers will be able to provide measurements related to the disclosure.